Role of Elastography In Differentiating Malignant and Benign Thyroid Nodules Using Fine Needle Aspiration Cytology (Fnac) As Gold Standard - Hussain, Rashid; Ashraf, Muhammad; Pervaiz, Saman (Pakistan Armed Forces Medical Journal, 2025)
Objective: to determine the efficacy of elastography in differentiation of malignant and benign thyroid nodules using fine needle aspiration cytology (FNAC) as gold standard.Study Design: Analytical cross-sectional study.Place and Duration of Study: Department of Radiology, Combined Military Hospital (CMH), Rawalakot, Pakistan, from Oct 2022 to Mar 2023.Methodology: A total of 150 patients having one or more solid thyroid nodules diagnosed on conventional ultrasound were enrolled in the study. After obtaining informed consent, all patients underwent strain elastography under standard protocol and findings of strain elastography were compared with cytological findings.Results: There were 69(85.2%) patients who had malignant lesions on elastography as well as FNAC positive (true positive) while 59(85.5%) patients had non-malignant lesion on elastography as well as negative FNAC (true negative). The sensitivity and specificity was 85.2% and 85.5%, respectively. Positive and negative predictive values were 87.3% and 83.1%, respectively while overall accuracy was 85.3%.Conclusion: Elastography or strain elastography have high efficacy to differentiate malignant thyroid nodules and benign thyroid nodules and can be used in replacement of fine needle aspiration cytology (FNAC).